Social Work in Brazil in the Vortex of Three crises: Pandemic, Social and Political. - Garcia, Maria Lúcia Teixeira; Spolander, Gary; Barbosa, Rafael da Silva (British Journal of Social Work, 2023)
Social work in Brazil advocates a radical and critical model of social work theorisation and practice. This article explores the Brazilian theoretical and practice model, identifying the profession as being in the vortex of Covid-19, increasing state economic austerity, attacks on previously hard-won progressive social policy and increasing inequality and precarity. This provides a challenging practice environment. The professional re-conceptualisation model proposes that social work needs to fully theorise social difficulties to ensure that the profession intervenes to address the causes of the problems, rather than manifestations underlying them. This is undertaken through aligning itself with working-class conflicts, promoting rights and refusing to accept the rolling back of support already won. The Brazilian framework, located within its social realities, offers an opportunity for social work globally to consider what lessons can be learnt, to recognise the uniqueness of its perspectives and provide solidarity through its recognition.